Influence of Tannin Extracts on Hematological and Production Properties of Male Rabbits Fed Mycotoxin Diets - Aseel Adnan Abdulhussein; Mohammed Munis Dakheel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Tannins, as secondary metabolism of plant products, have several beneficial properties, such as antioxidant, antibacterial, and antifungal capabilities. These features have been used by the industry to improve animal performance.Twenty-eight healthy local male rabbits were weighted (average 1382.7 g) the animals were divided regularly and equally into four groups, which contained control (fed basal diet), Mycotoxin group (fed contaminated diet), the third group was fed mycotoxinsdiets plus giving orally tannin extract (125 mg/ml), and the fourth treatment was given mycotoxinsdiets plus giving orally tannin extract (250 mg/ml).The results demonstrated that tannin extracts, both concentrations of either 125 or 250 mg/ml, caused considerable variations (p≤0.01) in weight growth when compared to the control or the mycotoxin group. The body weight of the groups, however, was unaffected by these concentrations. Furthermore, using these extracts on mycotoxin diets caused a change in the feed conversion ratio and feed intake among rabbit groups, with the tannin groups showing lower values than the others.On the other hand, when compared both groups, the mycotoxin and low dose of the tannin, with a high concentration of tannin extract, 250 mg/ml, revealed significant values in liver enzymes (ALT and AST). Additionally, the same treatment (250 mg/ml) significantly reduced creatinine and urea levels as compared to other groups.In conclusion, a high concentration of tannin extract, from black tea, showed beneficial effects on the productive trials, the biochemical properties in male rabbits that fed contaminated mycotoxin diets.